Generation of organo-alkaline earth metal complexes from non-polar unsaturated molecules and their synthetic applications - Watanabe, Kohei (2022)
Organomagnesium compounds, representated by the Grignard reagents, are one of the most classical yet versatile carbanion species which have widely been utilized in synthetic chemistry. These reagents are typically prepared via oxidative addition of organic halides to magnesium metals, via halogen-magnesium exchange between halo(hetero)arenes and organomagnesium reagents or via deprotonative magnesiation of prefunctionalized (hetero)arenes. On the other hands, recent studies have demonstrated that the organo-alkaline earth metal complexes including those based on heavier alkaline earth metals such as calcium, strontium and barium could be generated from readily available non-polar unsaturated molecules such as alkenes, alkynes, 1,3-enynes and arenes through unique metallation processes. Nonetheless, the resulting organo-alkaline earth metal complexes could be further functionalized with variety of electrophiles in various reaction modes. Especially, organocalcium, -strontium and barium species have shown unprecedented reactivity in the downstream functionalization, which could not be observed in the reactivity of organomagnesium complexes. This perspective will focus on the newly emerging protocols for the generation of organo-alkaline earth metal complexes from non-polar unsaturated molecules and their applications in chemical synthesis and catalysis.